Topology and evolution of international trade network for fish and fish products - Liu, Honghong; Zhang, Shucheng; Mu, Yongtong; Zhu, Yugui (Frontiers in Sustainable Food Systems, 2023)
In this study, complex network methods were employed to quantify the changing roles of countries in fish trade and the dynamic characteristics of fish globalization. Based on trade data from UN Comtrade, ITN-Fish was constructed as a series of weighted-directed networks for each year from 1990 to 2018. Almost all countries and territories in the world have been involved in the fish trade, and the network identified 229 fish traders in 2018. From 1990 to 2018, new trade relations were improving the network connectivity. However, these relations carried a small share of fish trade, and high connectivity allowed risks to be rapidly transmitted to the globe through hubs such as the U.S. and China, raising concerns about the robustness of these weak links in the event of U.S.-China trade conflict and COVID-19 pandemic. But we have optimistic expectations for this issue. Dynamics of network topology properties showed that the globalization of fish trade was thriving during 1990-2018 and was characterized by different patterns in periods 1990-2000 and 2004-2018, with 2001-2003 as a transition period. When total fish trade declined in 2009 and 2015 due to financial crisis, the structure of the network was not seriously affected, and the trend of topology properties did not change as a result. In addition, developing countries have increased their share in both imports and exports, mainly due to several major traders, such as China and Vietnam. And China have shifted from net exports to trade balance.